Problems and prospects for reducing statelessness in the Republic of Kazakhstan - Turlayev, A.V.; Sopykhanova, A.B. (Bulletin of the Karaganda University “Law Series”, 2024)
The article discusses the problematic issues of legal regulation and statelessness reducing practice in the Republic of Kazakhstan. Statelessness reduction is considered as a political, economic, and legal process that is important for the legal state, in which universal standards in the citizenship sphere are implemented. The research purpose is a comprehensive analysis, theory and practice synthesis of reducing statelessness in Kazakhstan, as well as identifying the problems of reducing statelessness legal regulation and developing ways to solve them. The research is carried out by general scientific and special legal methods, theoretical provisions and legal norms analysis and generalization. The statelessness reduction is considered as a political phenomenon with a legal form. On the comparative legal method basis, the main trends in the development in “reduction of statelessness” institution at the present time are revealed. The main result of the research is the provision on the need to improve legal measures aimed at reducing statelessness in Kazakhstan legislation. To conclude, it is proposed to supplement the family law legal norms, legislation on citizenship and by-laws that determine the stateless person legal status.